Auriculopuncture decreases anxiety levels in Chilean adults with malnutrition by excess - Maury-Sintjago, Eduard Antonio; Robledo-Larenas, Javiera; Pinto-Gallardo, Jennifer; Rodríguez-Fernández, Alejandra (Universidad y Salud, 2018)
Introduction: Despite the increase in the use of traditional Chinese medicine for the treatment of obesity, there are few studies which evaluate its effect. Objective: To determine the effect of auriculopuncture on anxiety, nutritional intake and anthropometric measures in Chilean adults with malnutrition by excess. Materials and methods: A quasi-experimental study was conducted with a probabilistic sample conformed by 21 subjects, divided into two groups: intervened GI (n=11) and control GC (n=10). The intervention consisted in performing auriculopuncture for seven weeks to GI and administering a placebo to GC. In both groups anthropometry, nutritional intake and anxiety levels were determined. All participants signed informed consent. To compare averages between groups and intra groups, the T-student test was used for paired samples. Statistical significance was set to one (α < 0.05). Results: A decrease in anxiety (p=0.036) and sodium intake (p=0.035) was found in the GI. No statistically significant differences were found in the variables of caloric-nutritional and anthropometric intake in any group. Conclusions: It is necessary to increase the intervention time to evaluate the long-term effect and thus establish causal associations.